Promoting EFL Learners’ Listening Comprehension through Digital Sory-Telling - Wati, Laila; Hamburabbi, Muhammad; Wathani, Hamzani; Nazri, M. Adib; Maysuroh, Siti (Institut Agama Islam Negeri Ponorogo, 2024)
This research is aimed at finding out the effectiveness of digital story-telling in teaching listening at the second semester of Hamzanwadi University. This research is a quantitative research employing pre-exprimental design using one group pre-test and post-test. The sample of this study was 20 students of the second semester class 2d. The data were collected from students pre-test and post-test. The tests were multiple choice. The data were analyzed by using SPSS 22 for Windows. After submitting the data to a paired sample t-test, it was found that there was a significant difference in the mean score in the pre-test and the post-test which was t(df=17)=-30.000 at p=0.000. This means that the hypothesis proposed was proven to be accepted. Besides, the students could more easily grasp meaning especially when the story-telling was presented by video and some keywords related to the material. The activities were also more varied because the students worked more in groups. In short, digital story-telling was significantly effective in teaching listening at the second semester of the English Language Educatioan Study Program in Hamzanwadi University. Thus, it is recomended that English lecturers and teachers use this media in teaching listening.